Meter-scale multi-loop capillary heat pipe. (August 2018) - Okazaki, Shun; Fuke, Hideyuki; Ogawa, Hiroyuki; Miyazaki, Yoshiro; Takahashi, Katsumasa; Yamada, Noboru
Highlights: A new heat pipe system is proposed. The heat pipe comprises multi-loop capillary tubes and a reservoir. The system transfers heat in a meter-scale between two vertical plates. The heat pipe temperature is maintained below the reservoir temperature. Experimental data and simple calculations verify the designed heat-pipe scheme. Abstract: In this study, a newly proposed heat pipe system was investigated to transfer heat from a vertical heated plate to a vertical cooled plate arranged in parallel. The heat pipe system comprises 32 loops connected in series and a reservoir. Each square-shaped loop (with a side length of 2 m) comprises a capillary tube with an inner diameter of 1.0 mm without any internal wick. The system's overall thermal performance was investigated at room temperature using R410A as the working fluid. Temperatures, pressures, and reservoir weight were monitored, and thereby confirming that the system transfers heat up to several hundred watts by a passive two-phase flow. Numerical simulations with a simple model were consistent with the data and verified that the saturated pressure of the system is controlled by the reservoir temperature independent of the amount of heat load.